Evolution of competitive ability and the response to nutrient availability: a resurrection study with the calcareous grassland herb, Leontodon hispidus - Pascal Karitter; Emma Corvers; Marie Karrenbauer; Martí March-Salas; Bojana Stojanova; Andreas Ensslin; Robert Rauschkolb; Sandrine Godefroid; J. F. Scheepens (Oecologia, 2025)
Rapid environmental changes across Europe include warmer and increasingly variable temperatures, changes in soil nutrient availability, and pollinator decline. These abiotic and biotic changes can affect natural plant populations and force them to optimize resource use against competitors. To date, the evolution of competitive ability in the context of changes in nutrient availability remains understudied. In this study, we investigated whether the common calcareous grassland herb Leontodon hispidus recently evolved its competitive ability and response to nutrient availability. We compared ancestors sampled in 1995 and descendants sampled in 2018 and applied a competition treatment in combination with weekly nutrient treatments (no fertilizer, nitrogen, phosphorus, and both). We found evidence for evolution of increased competitive ability, with descendants producing more vegetative biomass than ancestors when grown under competition. Furthermore, supplementing nutrients (especially N) reduced differences in competitive ability between ancestors and descendants, suggesting that nutrients are a limiting factor in interspecific competition, which could be linked to the decreasing nitrogen emissions into the atmosphere since the 1990s. Our study demonstrates rapid contemporary evolution of competitive ability, but also the complexity of the underlying processes of contemporary evolution, and sheds light on the importance of understudied potential selection agents such as nutrient availability.